Biodegradable star HPMA polymer-drug conjugates: Biodegradability, distribution and anti-tumor efficacy - Etrych, Tomáš; Kovář, Lubomír; Strohalm, Jiří; Chytil, Petr; Ríhová, Blanka; Ulbrich, Karel (Journal of controlled release, 2011)
Herein, new biodegradable star polymer-doxorubicin conjugates designed for passive tumor targeting were investigated, and their synthesis, physico-chemical characterization, drug release, biodegradation, biodistribution and in vivo anti-tumor efficacy are described. In the conjugates, the core formed by poly(amidoamine) (PAMAM) dendrimers was grafted with semitelechelic N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers bearing doxorubicin (Dox) attached by hydrazone bonds, which enabled intracellular pH-controlled drug release. The described synthesis facilitated the preparation of biodegradable polymer conjugates in a broad range of molecular weights (200-1000g/mol) while still maintaining low polydispersity (~1.7). The polymer grafts were attached to the dendrimers through either stable amide bonds or enzymatically or reductively degradable spacers, which enabled intracellular degradation of the high-molecular-weight polymer carrier to excretable products. Biodegradability tests in suspensions of EL4 T-cell lymphoma cells showed that the rate of degradation was much faster for reductively degradable conjugates (close to completion within 24h of incubation) than for conjugates linked via an enzymatically degradable oligopeptide GFLG sequence (slow degradation taking several days). This finding was likely due to the differences in steric hindrance in terms of the accessibility of the small molecule glutathione and the bulky enzyme cathepsin B to the polymer substrate. Regarding drug release, the conjugates were fairly stable in buffer at pH 7.4 (model of blood stream) but released doxorubicin under mild acidic conditions that model the tumor cell microenvironment. The star polymer-Dox conjugates exhibited significantly prolonged blood circulation and enhanced tumor accumulation in tumor-bearing mice, indicating the important role of the EPR effect in its anti-cancer activity. The star polymer conjugates showed prominently higher in vivo anti-tumor activities than the free drug or linear polymer conjugate when tested in mice bearing EL4 T-cell lymphoma, with a significant number of long-term surviving (LTS). Based on the results, we conclude that a M(w) of HPMA copolymers of 200,000 to 600,000g/mol is optimal for polymer carriers designed for the efficient passive targeting to solid tumors. In addition, an expressive therapy-dependent stimulation of the immune system was observed.
Keywords: doxorubicin; lidé; Biocompatible Materials; methakryláty; Dendrimers; Lymphoma; Cell Line, Tumor; Antibiotics, Antineoplastic; Doxorubicin; myši; Humans; lymfom; Mice; protinádorová antibiotika; biokompatibilní materiály; Methacrylates; zvířata; Animals; dendrimery; nádorové buněčné linie